Assessment of Educational Tools in the Online Modality - Fuentes Panameño, Diana Edith; Lopez Orellana, Liliana Lissette; Murillo Tejada, Ana Milagro (2024)
Students of the Foreign Language Department have the opportunity to graduate from UES through the e-learning specialization course. This is a new option that emerged because of the covid-19 pandemic. Even though, the coronavirus Disease (COVID-19) outbreak poses serious concerns to global education systems. Efforts to contain COVID-19 prompted the unscheduled closure of schools in more than 100 countries worldwide. This course also shows that many educators and students relied on technology to ensure continued learning online during the Coronavirus pandemic. In this document, the research team will explore the different teaching techniques using different learning management systems and educational tools that contemplate the teaching through virtual environments, theories of learning and teaching the change of role from student to the teacher will be analyzed in the present report. This one will be a unique opportunity to put into practice and implement a new methodology for students from the UES language department, in order to obtain their university degree, not only with a thesis but also with a specialization in virtual environments that are very important nowadays. Key words: E-learning ; Synchronous and asynchronous learning ; Learning Management System (LMS) ; Educational tolos ; Platform ; Online education ; Virtual classroom ; Virtual environment.